Gamma radiation of quartz from Entre Rios (SC) and Quaraí (RS) (Brazilian Journal of Radiation Sciences (BJRS), 2019)
The availability of gamma ray irradiators in Brazil increased the possibilities of treatments of gemstones for color   enhancements. One of the minerals with a very high potential of these treatments is quartz, a very widespread mineral with many colored commercial varieties.  A specific variety of quartz showing a green color in nature or induced artificially by radiation gamma (60Co) is quite rare. In Brazil the widely scattered geode occurrences from Quaraí at Brazil southernmost tip to Uberlandia in Minas Gerais is one of these. Quartz from these occurrences have been formed by strong hydrothermal activities. That way much quartz crystals showed a very fast growth history facilitating the  formation of growth defects and the uptake of water in form of micro inclusions, molecular water, silanol (Si-OH) and OH. In the present work the material analyzed is from hydrothermal regimes  located near the towns Entre Rios and Quaraí. To characterize these materials  analyses have been made by ICP, NAA, electron microscopy, water loss  techniques and UV-VIS and NIR-FTIR spectroscopic measurements. Silanol complexes are found, which by radiation due to gamma rays form the color center NBOHC (Non-Bonding Oxygen Hole Center), showing absorption between 590 to 620 nm and leaving a transmission window at about 550nm, responsible for the green color. The spectroscopic water determination showed less molecular water (up to 2300 ppm by weight), probably due to remaining silanol complexes.The water content with up to 3200 ppm by weight exceeds the amount of charge balancing cations (Fe, Al, Li).